سوشل میڈیا اور اسلامی جمہوریہ پاکستان : ثقافتی مبارزہ،چیلنجزاور ممکنہ حل: Social Media and the Islamic Republic of Pakistan: Clash of Civilizations, Challenges and Possible Solutions - Khan, Hafiz Ullah; Fakhr ud-din, Dr. Muhammad (Al-Amīr Research Journal for Islamic Studies, 2023)
This research explores the dynamic interaction between social media and the Islamic Republic of Pakistan, revealing a complex culture war unfolding in the digital landscape. The study examines how social media platforms have become arenas of competition, where traditional Islamic values collide with the global influence of digital communication. By examining the ways in which social media have shaped and reflected Pakistani cultural identity, the research examines the tension between modernity and conservatism, as well as challenges to established social norms. Additionally, it analyzes the role of social media in promoting communication, political discourse, and diverse voices in the context of Pakistan’s cultural landscape. By shedding light on this culture war, this research contributes to understanding the complex relationship between social media and the Islamic Republic of Pakistan. Keywords: Social media, Islamic Republic of Pakistan, Clash of Civilizations, digital communication, Islamic Culture.